Analisis Strategi Pengelolaan Biaya Operasional Dalam Peningkatan Efisiensi (BOPO) Pada KSPPS Zam-Zam Barokah Cilongok Pendekatan SERVO Analysis - Anisatul Amalia; Ita Solihatun; M. Irwan Farouki; Nindita Septiana Putri; Sutriawati Sutriawati; Sulasih Sulasih (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze operational cost management strategies in improving efficiency (BOPO) at KSPPS Zam-Zam Barokah Cilongok using the SERVO Analysis approach, which includes five key elements: Strategy, Environment, Resource, Value, and Organization. The method used in this research is descriptive qualitative by means of in-depth interviews with KSPPS internal sources. The results of this study indicate that the efficiency strategy implemented by the institution has been effective, achieving a SERVO Index score of 4.08, categorized as good. KSPPS Zam-Zam Barokah Cilongok has successfully applied efficiency strategies through digital innovations such as the BMT Collector application, cost control, and resource optimization. However, further strategic improvements are required through product diversification, human resource capacity development, and member network expansion to enhance efficiency and institutional competitiveness.